2015
DOI: 10.2105/ajph.2014.302368
|View full text |Cite|
|
Sign up to set email alerts
|

Fast-Food Fights: News Coverage of Local Efforts to Improve Food Environments Through Land-Use Regulations, 2000–2013

Abstract: Zoning and other land-use policies are a promising but controversial strategy to improve community food environments. To understand how these policies are debated, we searched existing databases and the Internet and analyzed news coverage and legal documentation of efforts to restrict fast-food restaurants in 77 US communities in 2001 to 2013. Policies intended to improve community health were most often proposed in urban, racially diverse communities; policies proposed in small towns or majority-White communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 13 publications
2
22
1
Order By: Relevance
“…Our findings are at odds with the rationale behind policy interventions that seek to restrict establishment of fast food restaurants in order to improve the dietary behavior of consumers (Nixon et al, 2015). This rationale posits that restriction of fast food restaurants would reduce intake of unhealthy foods, and understates the importance of underlying taste preferences that drive overall eating behavior.…”
Section: Discussioncontrasting
confidence: 62%
“…Our findings are at odds with the rationale behind policy interventions that seek to restrict establishment of fast food restaurants in order to improve the dietary behavior of consumers (Nixon et al, 2015). This rationale posits that restriction of fast food restaurants would reduce intake of unhealthy foods, and understates the importance of underlying taste preferences that drive overall eating behavior.…”
Section: Discussioncontrasting
confidence: 62%
“…A patient’s environment may change without any migration because of the opening and closing of retail food outlets, which we refer to as neighborhood change. Accessibility within 3 miles may be particularly relevant for food stores, given that multiple studies show that individuals travel between two and four miles from home to shop for groceries (4,610). Accessibility within 1 mile may be more relevant for fast food restaurants where individuals often purchase prepared foods or snacks for home consumption.…”
Section: Designmentioning
confidence: 99%
“…Most subsidy programs target supermarkets because they offer the widest selection of healthy foods(47). In another direction, some governments are trying to reduce access to unhealthy food using fast food restaurant moratoriums and zoning policies that restrict or ban new fast food restaurants in so-called over-served neighborhoods(810). In other places, local zoning laws and ordinances include store size restrictions, design guidelines, and formula business regulations(11,12) restrict the entry of the supercenters and other mass merchandisers that are a primary source of food for American households (i.e., Walmart, Target, and other large stores that sell a large variety of food and non-food merchandise)(13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Second, the constant media attention to high-calorie menu items and fast food in particular 19 may spur voluntary reformulation of menu items. For example, a recent article in the New York Times showed that the typical order at Chipotle contains about 1,070 calories—twice as many calories as a Big Mac and “more than half of the calories that most adults are supposed to eat in an entire day.” 20 …”
Section: Policy Implicationsmentioning
confidence: 99%